An Analysis of Appreciative Intelligence to Time Management on Successful Millennials as The Culinary Business Owner in Bandung - Pratiwi, Risa; Wisesa, Anggara (Journal of Innovation, Business and Entrepreneurship, 2017)
Abstract. The data of the Ministry of Cooperatives & SME at the end of 2015 showed that culinary business has the largest contribution to GDP. The owner of successful culinary business are mostly millennials. There must be some factors which influence those people to be success in business. This research is qualitative research conducted to explore objective of the study. Qualitative method was chosen since this research objective is to explore how AQ playing role in time management especially in Millennial generation as culinary business owner in Bandung. The research found that the more productive they are, the higher their ability to reframe, appreciate the positive, and see the future unfold from present. The research findings toward those with high productivity is a result of how long they have been attached to their commitment to be an entrepreneur so it leads them to get used to self-discipline and it demands them to have a good time management by planning, organizing, and prioritizing their activity.